Identifikasi Morfologi Kantong Semar Di Wilayah Gunung Bitung, Kabupaten Ciamis - Feby Nurul Asri; Luthfi Hana Fadiah; Nabila Nur’ Arifah; Ateng Supriyatna (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
Nepenthes sp. is one of the plants that has a distinctive size and shape found in the color pattern, shape of the bag, and its ability to catch insects., the semar bag (Nepenthes spp.) is a protected plant. The purpose of this study was to determine the type of morphology of semar bags in the Cibitung Mountain area. This type of research is an exploratory description, which explores the Mount Cibitung area and identifies morphological characteristics such as shape, leaves, flowers, and semar pouches. The results of this study reveal that one species of Nepenthes miribilis can be found in the Mount Cibitung area, Ciamis. nepenthes miribilis A species of creeping or climbing plant with a height of approximately 3 meters, smooth round stems with clear internodes and purplish green stems, lanceolate-shaped leaves that are stemmed and elliptical have pointed or tapered leaf tips, and stemless rosette-shaped leaves with short stalks. Toothed or hairy leaf edges. The upper surface of the leaf is light green